2019
DOI: 10.1016/j.jse.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Coracoacromial morphology: a contributor to recurrent traumatic anterior glenohumeral instability?

Abstract: Background: While scapular morphology contributes to glenohumeral osteoarthritis and rotator cuff disease, its role in traumatic glenohumeral instability remains unknown. We hypothesized that coracoacromial and glenoid morphology would differ between healthy subjects and those with recurrent traumatic anterior shoulder instability.Methods: Computed tomographic scans of 31 cadaveric control scapulae and 54 scapulae of patients with recurrent traumatic anterior shoulder instability and Hill-Sachs lesions were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…40,41 Owens et al 20 found that the coracohumeral distance was an independent risk factor for traumatic anterior shoulder instability, with an increased risk of instability of 20% for every 1-mm increase in coracohumeral distance. This was further confirmed by Jacxsens et al, 42 who found a more medial and superior orientation of the coracoid process in patients with anterior instability as compared to nonpathologic shoulders, suggesting that a difference in the position of the coracoid process and its attaching soft tissue alter the stabilizing function of the conjoined tendon in the shoulder. On the basis of the substantial shape variation around the coracoid seen in modes 4 and 5, differences in coracohumeral distance can be explained by an underlying deviation of the coracoid process.…”
Section: Discussionsupporting
confidence: 58%
“…40,41 Owens et al 20 found that the coracohumeral distance was an independent risk factor for traumatic anterior shoulder instability, with an increased risk of instability of 20% for every 1-mm increase in coracohumeral distance. This was further confirmed by Jacxsens et al, 42 who found a more medial and superior orientation of the coracoid process in patients with anterior instability as compared to nonpathologic shoulders, suggesting that a difference in the position of the coracoid process and its attaching soft tissue alter the stabilizing function of the conjoined tendon in the shoulder. On the basis of the substantial shape variation around the coracoid seen in modes 4 and 5, differences in coracohumeral distance can be explained by an underlying deviation of the coracoid process.…”
Section: Discussionsupporting
confidence: 58%
“…Recurrent traumatic AGI was significantly associated with a shorter coracoid, oriented more superomedial. Furthermore, the origin of the coracoid on the glenoid was located more posteriorly, closer to the 12 o'clock position than the 3 o'clock position 2 (Fig. 2).…”
Section: Anatomical Rationalementioning
confidence: 88%
“…Mean shape differences between a control group and a pathologic unstable scapula group according to a statistical shape modeling developed by Jacxsens et al 2 Blue arrows indicate an increase, whereas yellow arrows denote a decrease between the illustrated mean shape of the control group and the mean shape of the unstable group. The size of the arrow represents the magnitude of the morphologic differences.…”
Section: Anatomical Rationalementioning
confidence: 99%
See 2 more Smart Citations